2018
DOI: 10.1021/jacs.8b08547
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Benzylic C–H Trifluoromethylation for Late-Stage Functionalization

Abstract: The installation of trifluoromethyl groups has become an essential step across a number of industries such as agrochemicals, drug discovery, and materials. Consequently, the rapid introduction of this critical functional group in a predictable fashion would benefit current practitioners in those fields. This communication describes a mild trifluoromethylation of benzylic C−H bonds with high selectivity for the least hindered hydrogen atom. The reaction provides monotrifluoromethylation and proceeds in an envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
74
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 68 publications
(53 reference statements)
2
74
0
2
Order By: Relevance
“…Nevertheless, this protocol was applicable only to primary C(sp 3 )-H bonds with electron-rich substitution on the aromatic ring. A variant of the method with the use of (bpy)Cu(CF 3 ) 3 , (NH 4 ) 2 S 2 O 8 , and i Pr 3 SiH was published by the Cook group 32 during the preparation of this work (Scheme 1A). However, it requires the use of UV (365 nm) light and the use of excess (2 equiv) alkylarenes as substrates, and the yields are based on the copper complex.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this protocol was applicable only to primary C(sp 3 )-H bonds with electron-rich substitution on the aromatic ring. A variant of the method with the use of (bpy)Cu(CF 3 ) 3 , (NH 4 ) 2 S 2 O 8 , and i Pr 3 SiH was published by the Cook group 32 during the preparation of this work (Scheme 1A). However, it requires the use of UV (365 nm) light and the use of excess (2 equiv) alkylarenes as substrates, and the yields are based on the copper complex.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Aside from ah andful of CF 3 -radical-based functionalizations of structurally elaborated styrene derivatives, [4] these molecules could be created either by direct trifluoromethylation of aliphatic skeletons [5] or through crosscoupling using a-CF 3 -derived precursors (Scheme 1a). [6,[12][13][14][15][16] With Lisp ioneering work on trifluoromethylation of alkyl radicals using Grushinsreagent, [7] thegroups of MacMillan, [8] Cook, [9] and Liu, [10] developed decarboxylative and benzylic C À Ht rifluoromethylation protocols,a lthough the employment of expensive CF 3 reagents,aswell as restricted substrate scope,are still concerns.…”
mentioning
confidence: 99%
“…Examination of different photocatalysts showed that the use of [Ir(dF(CF 3 )ppy) 2 (5,5'-dCF 3 bpy)](PF 6 )( PC-V, E 0 1/ 2 III*/II =+1.69 Vv s. SCE in MeCN) [23] enabled the best balance between reaction yield and selectivity,a lbeit with moderate conversion (entries 1-6). Further fine tuning the reaction conditions eventually led to the formation of 3a in 79 %y ield (entries [9][10][11]. Notably,c ontrol experiments indicated the vital importance of the photocatalyst and light irradiation in this protocol (entries 7a nd 8).…”
mentioning
confidence: 99%
“…[12] Liu et al and our group disclosed benzylic C(sp 3 )ÀHt rifluoromethylation that can be employed for late-stage functionalization (Scheme 1c). [13] Here,wedescribe the simultaneous introduction of two trifluoromethyl groups across alkynes using bpyCu(CF 3 ) 3 , persulfate and blue light to access E-HFBs (Scheme 1d). Under irradiation, bpyCu(CF 3 ) 3 liberates one trifluoromethyl radical.…”
mentioning
confidence: 99%